There's No Place Like Ames: A redesign to create a safe and welcoming park in Lynn, MA. - Dickens, Joshua.; Eldridge, Lydia.; Kim, Yeojin.; Olins, Jasmine.; Spaman, Chelsea. (Tufts University. Tisch Library., 2023)
2022 M.A./M.S. in Urban and Environmental Policy and Planning Field Project. Client: City of Lynn.